Red and near-infrared absorbing dicyanomethylene squaraine cyanine dyes: photophysicochemical properties and anti-tumor photosensitizing effects - Martins, Tiago D. (2020)
Photodynamic therapy is a medical modality developed for the treatment of several diseases of oncological and non-oncological etiology that requires the presence of a photosensitizer, light and molecular oxygen, which combined will trigger physicochemical reactions responsible for reactive oxygen species production. Given the scarcity of photosensitizers that exhibit desirable characteristics for its potential application in this therapeutic strategy, the main aims of this work were the study of the photophysical and photochemical properties and the photobiological activity of several dicyanomethylene squaraine cyanine dyes. Thus, herein, the study of their aggregation character, photobleaching and singlet oxygen production ability, and the further application of the previously synthesized dyes in Caco-2 and HepG2 cancer cell lines, to evaluate their phototherapeutic effects, are described. Dicyanomethylene squaraine dyes exhibited moderate light-stability and, despite the low singlet oxygen quantum yields, were a core of dyes that exhibited relevant in vitro photodynamic activity, as there was an evident increase in the toxicity of some of the tested dyes exclusive to radiation treatments.